Low‐Dose Linaclotide (72 μg) for Chronic Idiopathic Constipation: A 12‐Week, Randomized, Double‐Blind, Placebo‐Controlled Trial. (January 2018) - Schoenfeld, Philip; Lacy, Brian E; Chey, William D; Lembo, Anthony J; Kurtz, Caroline B; Reasner, David S; Bochenek, Wieslaw; Tripp, Kenneth; Currie, Mark G; Fox, Susan M; Blakesley, Rick E; O'Dea, Christopher R; et al.
Abstract : OBJECTIVES: Linaclotide is a guanylate cyclase‐C agonist approved in the United States, Canada, and Mexico at a once‐daily 145‐μg dose for the treatment of chronic idiopathic constipation (CIC); a once‐daily 72‐μg dose for CIC recently received FDA approval. The trial objective was to evaluate the efficacy and safety of a 72‐μg linaclotide dose in CIC patients. METHODS: This double‐blind, placebo‐controlled trial randomized patients with CIC (Rome III criteria) to once‐daily linaclotide 72 μg or 145 μg, or placebo for 12 weeks. The primary endpoint, 12‐week complete spontaneous bowel movement (CSBM) overall responder, required patients to have ≥3 CSBMs and an increase of ≥1 CSBM per week from baseline in the same week for ≥9 of 12 weeks of the treatment period. Secondary endpoints included 12‐week change from baseline in bowel (SBM and CSBM frequency, stool consistency, straining) and abdominal (bloating, discomfort) symptoms, monthly CSBM responders, and 12‐week CSBM responders among patients who averaged >1 SBM/week at baseline. Sustained response (12‐week CSBM overall responders who met weekly criteria for 3 of the 4 final weeks (weeks 9–12) of treatment) was evaluated as an additional endpoint. Adverse events (AEs) were monitored. RESULTS: The intent‐to‐treat population included 1, 223 patients (mean age=46 years, female=77%, white=71%). The primary endpoint was met by 13.4% of linaclotide 72‐μg patients vs. 4.7% of placebo patients ( P <0.0001, odds ratio=3.0; statistically significant controlling for multiplicity). Sustained response was achieved by 12.4% of linaclotide 72‐μg patients vs. 4.2% of placebo patients (nominal P <0.0001). Linaclotide 72‐μg patients met 9‐of‐10 secondary endpoints vs. placebo ( P <0.05; abdominal discomfort, P =0.1028). Patients treated with linaclotide 145 μg also improved CIC symptoms for the primary (12.4%) and sustained responder endpoint parameters (11.4%) and for all 10 of the secondary endpoint parameters including abdominal discomfort ( P <0.05). Diarrhea, the most common AE, was mild in most instances and resulted in discontinuation of 0, 2.4%, and 3.2% of patients in the placebo, linaclotide 72‐μg, and linaclotide 145‐μg groups, respectively. CONCLUSIONS: Once‐daily linaclotide 72 μg significantly improved CIC symptoms in both men and women with a low rate of discontinuation due to diarrhea over 12 weeks of treatment.